(untitled) (Aporia, 2017)
In this paper, I give a semantic solution to what is usually called the "problem of induction". This solution is directly inspired by the non-related literature on epistemic contextualism, the view that ’know’ is context-sensitive. I first present the problem of induction and Popper’s response. I then argue that ’x is justified in believing p’ is indexical, which provides a solution to the problem of induction. I then consider two counterarguments to my thesis: that my solution is not a real solution; and, more importantly, that x is never justified in believing that the future will resemble the past. I show these two counterarguments to be inconclusive and I conclude that my semantic solution is a genuine answer to the problem of induction.